Strong soy protein isolate-based film and its preparation process and application using pulsed electric field precise control

By adding bisaldehyde starch and polyvinyl alcohol in the preparation process of soy protein isolate film and reacting under the action of pulsed electric field, the problem of poor mechanical properties of soy protein isolate film is solved, and film materials with high strength, high toughness and excellent ultraviolet barrier properties are achieved.

CN116875066BActive Publication Date: 2025-03-18SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310669755.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-03-18
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

The poor mechanical properties of existing soy protein isolate-based films limit their industrial production applications, and traditional improved methods such as the addition of glycerol or chemical crosslinking agents will lead to reduced flexibility of the material or have certain toxicity.

Method used

A strong soy protein isolate film was prepared by mixing soy protein isolate solution, bisaldehyde starch solution and polyvinyl alcohol solution, adjusting the pH to 8.5-11, and reacting at 60-100°C and a pulsed electric field for 10-50 minutes.

Benefits of technology

It achieves high tensile strength, elongation of break and high toughness of soy protein isolate films, and has excellent ultraviolet barrier properties, which are suitable for food active packaging and ultraviolet protection materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116875066B_ABST
    Figure CN116875066B_ABST
Patent Text Reader

Abstract

The present invention discloses a strong and tough soy protein isolate-based film and its preparation process and application using a pulsed electric field for precise control. The strong and tough soy protein isolate-based film is prepared by mixing a soy protein isolate solution, a dialdehyde starch solution and a polyvinyl alcohol solution, adjusting the pH to 8.5-11, reacting for 10-50 minutes at 60-100°C and under the action of a pulsed electric field, and pouring the product into a culture dish, and drying the obtained product; the soy protein isolate-based film prepared by the present invention has excellent mechanical properties compared to other biomass film materials (cellulose, starch and chitosan films), the tensile strength of the material can reach 18.3MPa, and the elongation at break can reach 240.5%, which is 631% and 654% higher than the tensile strength and toughness of the soy protein isolate film with the addition of a traditional glycerol plasticizer; the obtained soy protein isolate-based film can block 97%-100% of the ultraviolet transmittance (≤400nm).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a protein-based film, in particular to a strong soy protein isolate-based film and a preparation process and application thereof using precise control of a pulse electric field; and belongs to the field of biodegradable material development. Background Art

[0002] With the development of science and technology and the implementation of sustainable development strategies, biodegradable materials have attracted more and more attention. Among biopolymers, soy protein isolate is a renewable, environmentally friendly, highly processable biopolymer with rich functional groups; therefore, it is a good alternative to synthetic polymers for the development of environmentally friendly composite films. However, due to the strong hydrophilicity and molecular interactions of natural soy protein isolate, the film-forming property, mechanical properties and toughness of the resulting films are poor, which greatly limits the application of soy protein-based films. Therefore, small molecule plasticizer glycerol is added to reduce the strong intermolecular / intramolecular interactions between soy protein molecules and increase the mobility of protein chains. However, while glycerol-plasticized soy protein increases flexibility, it also reduces film strength, and due to thermodynamic effects, glycerol plasticizers can easily migrate out of the protein matrix when exposed to the external environment. Subsequently, various chemical crosslinking agents, such as formaldehyde, glutaraldehyde, glyoxal and epoxy resin compounds, have been used to improve the mechanical properties of soy protein isolate films. However, the resulting films have significantly reduced ductility and have certain toxicity. Therefore, it remains challenging to develop soy protein film materials with both high strength and good ductility.

[0003] As can be seen from the above background technology, the current soy protein isolate-based film mainly has the problem of poor mechanical properties, which limits its industrialization and large-scale production and application. Other protein films have many deficiencies in cost and performance. Chinese invention patent CN103627033B discloses a prolamin-starch-based degradable composite film and a preparation method thereof, and its components and weight portions are: 100 parts of starch, 10-15 parts of prolamin, 6-10 parts of glycerol, and 5-8 parts of palygorskite clay. This technology utilizes the good compatibility of prolamin and starch. Adding a small amount of prolamin to the starch film can improve the strength of the plastic film while reducing the amount of glycerol. Adding palygorskite to the film is to improve the water retention performance of the composite material and reduce costs. Since starch-based materials have poor ductility, this invention improves the ductility of starch film by adding glycerol. However, the addition of glycerol will reduce the strength of the material. Moreover, due to the incompatibility between polymers and plasticizers, when the material is exposed to the external environment, changes in temperature, humidity, etc. can easily cause glycerol to migrate out of the material. The loss of glycerol will lead to reduced flexibility, embrittlement and cracking of the material. Secondly, the starch-based film prepared by this technology needs to be dried at 60°C for 20 hours after the mixed liquid is gelatinized for 30 minutes. After the film is removed, it needs to be vulcanized, sheeted and injection molded again using a hot press and a cold press. It is time-consuming, labor-intensive and energy-intensive, which limits its industrial and large-scale production and application. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art and meet the huge market demand for degradable biomaterials, the purpose of the present invention is to provide a strong soy protein isolate-based film with obvious performance advantages in tensile strength and ductility and a UV blocking rate of more than 99.9%, and a preparation process thereof using precise control of a pulsed electric field.

[0005] Another object of the present invention is to provide the use of the tough soy protein isolate-based film in the preparation of food active packaging or ultraviolet protection materials.

[0006] The purpose of the present invention is achieved through the following solutions:

[0007] A tough soy protein isolate based film is prepared by mixing a soy protein isolate solution, a dialdehyde starch solution and a polyvinyl alcohol solution, adjusting the pH to 8.5-11, reacting for 10-50 minutes at 60-100°C under the action of a pulse electric field, pouring the product into a culture dish and drying; the frequency of the pulse electric field is 100-1000Hz, the pulse width is 10-60μs, and the field strength is 2-15kV / cm.

[0008] To further achieve the purpose of the present invention, preferably, the mass content of the soy protein isolate solution is 1% to 10%.

[0009] Preferably, the mass content of the dialdehyde starch solution is 4% to 15%.

[0010] Preferably, the mass content of the polyvinyl alcohol solution is 5% to 20%.

[0011] Preferably, the mass ratio of the soy protein isolate to polyvinyl alcohol is 1:0.2-1.5, and the mass ratio of the soy protein isolate to dialdehyde starch is 2-9:1.

[0012] Preferably, the pH is adjusted to 8.5-11 by adding an alkaline solution, and the concentration of the alkaline solution is 0.05 mol / L-0.3 mol / L.

[0013] Preferably, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0014] Preferably, the drying is carried out in an oven at a drying temperature of 30 to 60° C. and a drying time of 10 to 30 hours.

[0015] The preparation process of the tough soy protein isolate-based film using pulsed electric field precise control comprises the following steps:

[0016] 1) mixing the soy protein isolate solution, the dialdehyde starch solution and the polyvinyl alcohol solution;

[0017] 2) adjusting the pH to 8.5-11, and pumping the mixed solution into a pulsed electric field at 60-100°C for 10-50 minutes;

[0018] 3) pouring the product obtained in step 2) into a culture dish and drying it to obtain a soy protein isolate-based film.

[0019] The tough soy protein isolate-based film is used in preparing food active packaging or ultraviolet protection materials.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] 1) On the one hand, polyvinyl alcohol as a soft component ensures the flexibility of the material. On the other hand, the present invention utilizes the treatment of pulsed electric field to unfold the structure of soy protein isolate, improve the flexibility of protein, expose more cross-linking sites, promote the covalent cross-linking and non-covalent bond (hydrogen bond) interaction between protein and aldehyde group, and the amino group of soy protein isolate reacts with the aldehyde group of dialdehyde starch to produce covalent cross-linking. Through covalent cross-linking, combined with a variety of non-covalent interactions, including hydrogen bonds, hydrophobic interactions, etc., an interconnected cross-linking network is constructed in the soy protein isolate-based film, which improves the strength and toughness of the film, thereby producing a soy protein isolate-based film with excellent tensile strength, high toughness and high ultraviolet shielding performance. The tensile strength of the soy protein isolate-based film can reach 18.3MPa, and the elongation at break can reach 240.5%, which is 654% higher than the toughness of the soy protein isolate film with only glycerol plasticizer added. The soy protein isolate-based film can block 97%-100% of the ultraviolet transmittance (≤400nm), and has great application value in anti-ultraviolet coating materials and tissue engineering.

[0022] 2) The soy protein isolate-based film of the present invention has excellent mechanical properties and good ultraviolet blocking properties. In addition, during the preparation process, the degree of expansion of the soy protein isolate structure is precisely controlled by adjusting the pulse energy, thereby achieving precise control of the range of the film's mechanical properties. Under low field strength (<4kV / cm), the toughness of the material can be controlled to be 19-27MJ / m 3 Under medium and high field strength (4-15kV / cm), the toughness of the material can be controlled to 27-25MJ / m 3 , to be applied to active packaging materials for different foods.

[0023] 3) Compared with other protein raw materials, the soy protein isolate of the present invention has obvious cost advantages. The present invention uses soy protein isolate to prepare a renewable, environmentally friendly and degradable soy protein isolate-based film, and the process flow of material processing is simple and can be suitable for industrial production. It has very obvious environmental advantages for replacing the non-degradable films of the prior art. At the same time, the present invention also solves the problem of mechanical properties of protein films, and has obvious market advantages.

[0024] 4) The present invention provides a simple and effective method for producing a degradable protein material with high strength and good ductility. Compared with other soy protein films, the film prepared by the present invention has improved mechanical properties and good UV blocking performance, showing potential application prospects in food active packaging, UV protective coatings and tissue engineering.

[0025] 5) Compared with other soy protein isolate-based films in the prior art, the tensile strength and ductility of the tough soy protein isolate-based film of the present invention are significantly improved, and a soy protein film material with high strength and good ductility is obtained, which is a biodegradable material, alleviating the pressure on the environment caused by the non-degradable petroleum-based plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the photoelectron spectrum of soy protein isolate (SPI).

[0027] Figure 2 This is the photoelectron spectrum of the soy protein isolate based film prepared in Comparative Example 3.

[0028] Figure 3 The stress-strain curves of the soy protein isolate-based films prepared in the examples and comparative examples.

[0029] Figure 4 It is a bar graph of the toughness of the soy protein isolate based films of the embodiments and comparative examples.

[0030] Figure 5 The ultraviolet light blocking properties of the soy protein isolate based films prepared in the examples and comparative examples. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] Example 1

[0033] (1) by adding distilled water to prepare 5% soy protein isolate solution and 4% dialdehyde starch solution, respectively, and adjusting the pH to 8.5 with 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0034] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0035] (3) 70 g of the soy protein isolate solution, 20 g of the dialdehyde starch solution, and 30 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and 0.1 M sodium hydroxide solution was added to adjust the pH to 9.5.

[0036] (4) maintaining the mixed solution in step (3) at 70° C., reacting under a pulsed electric field of 2 kV / cm for 20 min, and setting the pulse width and pulse frequency to 40 μs and 1000 Hz, respectively;

[0037] (5) The reactants in step (4) were poured into a culture dish and dried in an oven at 45° C. for 12 h to obtain a soy protein isolate-based film, which was named SPI / P / D-2.

[0038] After testing, the mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / P / D-2) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5 The tensile strength of the SPI / P / D-2 film is 13.70±0.51MPa, the elongation at break is 217.71±5.3%, and the toughness is 23.6MJ / m 3 , UV blocking rate is 99.04%.

[0039] Example 2

[0040] (1) by adding distilled water to prepare 5% soy protein isolate solution and 4% dialdehyde starch solution, respectively, and adjusting the pH to 9.5 with 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0041] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0042] (3) 70 g of the soy protein isolate solution, 20 g of the dialdehyde starch solution, and 30 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and the pH was adjusted to 10 using a 0.2 M sodium hydroxide solution.

[0043] (4) maintaining the mixed solution in step (3) at 70° C., reacting under a pulsed electric field of 4 kV / cm for 20 min, and setting the pulse width and pulse frequency to 20 μs and 500 Hz, respectively;

[0044] (5) The reactants in step (4) were poured into a culture dish and dried in an oven at 45° C. for 12 h to obtain a soy protein isolate-based film, which was named SPI / P / D-4.

[0045] After testing, the mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / P / D-4) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5The tensile strength of the SPI / P / D-4 film is 16.90±0.93MPa, the elongation at break is 220.92±10.3%, and the toughness is 27.4MJ / m 3 , UV blocking rate is 99.53%.

[0046] Example 3

[0047] (1) by adding distilled water to prepare 5% soy protein isolate solution and 4% dialdehyde starch solution, respectively, and adjusting the pH to 10 with 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0048] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0049] (3) 70 g of the soy protein isolate solution, 20 g of the dialdehyde starch solution, and 30 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and the pH was adjusted to 9.5 using a 0.3 M sodium hydroxide solution.

[0050] (4) maintaining the mixed solution in (3) at 70° C., reacting under a pulsed electric field of 6 kV / cm for 20 min, and setting the pulse width and pulse frequency to 60 μs and 800 Hz, respectively;

[0051] (5) The reactants in (4) were poured into a petri dish and dried in an oven at 45° C. for 12 h. A soy protein isolate-based film was obtained and named SPI / P / D-6.

[0052] After testing, the mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / P / D-6) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5 The tensile strength of SPI / P / D-6 film is 18.28±0.63MPa, the elongation at break is 240.53±3.9%, and the toughness is 36.2MJ / m 3 , UV blocking rate is 99.94%.

[0053] Example 4

[0054] (1) by adding distilled water to prepare 10% soy protein isolate solution and 15% dialdehyde starch solution, respectively, and adjusting the pH to 11 with 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0055] (2) In terms of mass percentage, a 20% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0056] (3) 60 g of the soy protein isolate solution, 5 g of the dialdehyde starch solution, and 15 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and the pH was adjusted to 11 using a 0.05 M sodium hydroxide solution.

[0057] (4) maintaining the mixed solution in step (3) at 100° C., reacting under a pulsed electric field of 15 kV / cm for 40 min, and setting the pulse width and pulse frequency to 10 μs and 100 Hz, respectively;

[0058] (5) The reactants in step (4) were poured into a culture dish and dried in an oven at 60° C. for 8 h to obtain a soy protein isolate-based film.

[0059] After testing, the soy protein isolate-based film obtained in the above steps has a tensile strength of 15.2±0.33MPa, an elongation at break of 183.36±2.7%, and a toughness of 25.4MJ / m 3 , UV blocking rate is 99.32%.

[0060] Comparative Example 1

[0061] (1) preparing a 5% soy protein isolate solution by adding distilled water, adjusting the pH to 9.5 using a 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0062] (2) 1.5 g of glycerol was added to 100 g of the soy protein isolate solution in (1), and the pH was adjusted to 9.5 using a 0.1 M sodium hydroxide solution.

[0063] (3) maintaining the mixed solution in (2) at 70° C. and reacting for 20 min;

[0064] (4) The reactants in (3) were poured into a petri dish and dried in an oven at 45° C. for 12 h. A soy protein isolate-based film was obtained and named SPI / G.

[0065] After testing, the mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / G) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5 The tensile strength of the SPI / G film is 2.5±0.23MPa, the elongation at break is 231±6.2%, and the toughness is 4.8MJ / m 3 , UV blocking rate is 63.3%.

[0066] Comparative Example 2

[0067] (1) preparing a 5% soy protein isolate solution by adding distilled water, adjusting the pH to 9.5 using a 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0068] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0069] (3) 70 g of the soy protein isolate solutions in (1) and (2) and 30 g of the polyvinyl alcohol solution were mixed, and the pH was adjusted to 9.5 using a 0.1 M sodium hydroxide solution.

[0070] (4) maintaining the mixed solution in (3) at 70° C. and reacting for 20 min;

[0071] (5) The reactants in (4) were poured into a petri dish and dried in an oven at 45° C. for 12 h. A soy protein isolate-based film was obtained and named SPI / P.

[0072] The mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / P) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5 The tensile strength of the SPI / P film is 7.06±0.36MPa, the elongation at break is 19.16±7.2%, and the toughness is 1.2MJ / m 3 , UV blocking rate is 79.02%.

[0073] Comparative Example 3

[0074] (1) by adding distilled water to prepare 5% soy protein isolate solution and 4% dialdehyde starch solution, respectively, and adjusting the pH to 9.5 with 0.1 M sodium hydroxide solution, and heating at 40° C. for 10 min;

[0075] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0076] (3) 70 g of the soy protein isolate solution in (1) and (2), 20 g of the dialdehyde starch solution, and 30 g of the polyvinyl alcohol solution were mixed, and the pH was adjusted to 9.5 using a 0.1 M sodium hydroxide solution.

[0077] (4) maintaining the mixed solution in (3) at 70° C.;

[0078] (5) The reactants in (4) were poured into a petri dish and dried in an oven at 45° C. for 12 h. A soy protein isolate-based film was obtained and named SPI / P / D-0.

[0079] The mechanical properties and UV blocking properties of the soy protein isolate based film (SPI / P / D-0) obtained in the above steps are as follows: Figure 3 , Figure 4 and Figure 5 The tensile strength of the SPI / P / D-0 film is 12.79±1.2MPa, the elongation at break is 194.95±4.1%, and the toughness is 19.1MJ / m 3 , UV blocking rate is 97.23%.

[0080] After testing, the photoelectron spectrum of the soy protein isolate based film (SPI / P / D-0) obtained in the above steps is as follows: Figure 2 As shown. Figure 1 It can be seen that the N1s spectrum of soy protein isolate (SPI) shows two main peaks at 399.36eV ​​(CN) and 400.6eV (NH). A new C=N characteristic peak was observed in the N1s spectrum of SPI / P / D-0 film, which is located at 399.37eV. This indicates that the amino group in SPI reacts with the aldehyde group in dialdehyde starch to form a -HC=N- functional group.

[0081] Comparative Example 4

[0082] (1) By adding distilled water, 8% soy protein isolate solution and 10% dialdehyde starch solution were prepared respectively, and the pH was adjusted to 10 with 0.1 M sodium hydroxide solution, and heated at 40° C. for 10 min;

[0083] (2) In terms of mass percentage, a 10% polyvinyl alcohol solution was prepared by adding distilled water and heating at 80° C. for 1 h to completely dissolve.

[0084] (3) 60 g of the soy protein isolate solution, 10 g of the dialdehyde starch solution, and 15 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and the pH was adjusted to 11 using a 0.1 M sodium hydroxide solution.

[0085] (4) maintaining the mixed solution in step (3) at 70° C., reacting under a pulsed electric field of 1 kV / cm for 40 min, and setting the pulse width and pulse frequency to 8 μs and 50 Hz, respectively;

[0086] (5) The reactants in step (4) were poured into a culture dish and dried in an oven at 60° C. for 8 h to obtain a soy protein isolate-based film.

[0087] After testing, the soy protein isolate-based film obtained in the above steps has a tensile strength of 12.8±0.23MPa, an elongation at break of 193.21±1.7%, and a toughness of 20MJ / m 3, UV blocking rate is 97.5%.

[0088] Comparative Example 5

[0089] (1) By adding distilled water, an 8% soy protein isolate solution and a 12% dialdehyde starch solution were prepared, respectively, and the pH was adjusted to 11 using a 0.1 M sodium hydroxide solution, and heated at 40° C. for 10 min;

[0090] (2) In terms of mass percentage, a 20% polyvinyl alcohol solution was prepared by adding distilled water and heated at 80°C for 1 hour to completely dissolve.

[0091] (3) 60 g of the soy protein isolate solution, 5 g of the dialdehyde starch solution, and 20 g of the polyvinyl alcohol solution in step (1) and step (2) were mixed, and the pH was adjusted to 9 using a 0.8 M sodium hydroxide solution.

[0092] (4) maintaining the mixed solution in step (3) at 90° C., reacting under a pulsed electric field of 18 kV / cm for 40 min, and setting the pulse width and pulse frequency to 100 μs and 2000 Hz, respectively;

[0093] (5) The reactants in step (4) were poured into a culture dish and dried in an oven at 60° C. for 8 h to obtain a soy protein isolate-based film.

[0094] After testing, the soy protein isolate-based film obtained in the above steps has a tensile strength of 10.9±0.43MPa, an elongation at break of 154.26±2.7%, and a toughness of 16.4MJ / m 3 , UV blocking rate is 95.93%.

[0095] The chemical structure characteristics of the raw material soy protein isolate (SPI) and the soy protein isolate-based film (SPI / P / D-0) prepared in the above comparative example 3 were measured using an X-ray photoelectron spectrometer (XPS). The test results are as follows: Figure 1 and Figure 2 As shown. XPS test method: The sample is fixed on the sample stage, and the monochromated AI-Kα ray (energy 1486.6eV) is used as the excitation light source, and its chemical composition is measured by X-ray photoelectron spectrometer. During the test, the spectrum of each element is recorded in the order of C1s, O1s, and N1s at a resolution of 0.05eV at a pass energy of 25eV. The obtained data is analyzed by XPS Peakfit 4.1 software.

[0096] The mechanical properties of the soy protein isolate based films prepared in the above examples and comparative examples were measured, and the test results are as follows: Figure 3 and Figure 4As shown. Mechanical properties test method: Cut the film into 70mm×10mm sample strips and use a universal testing machine with a 10kg load sensor to perform a tensile test. The tensile speed is set to 5mm / s, and the test is performed 8 times in parallel. The tensile strength, elongation at break, and toughness of different samples are measured and the average value is taken.

[0097] The ultraviolet barrier properties of the soy protein isolate based films prepared in the above examples and comparative examples were measured, and the test results are as follows: Figure 5 Test method: Cut the sample into 6cm×1cm strips, put them into a cuvette, and use a UV spectrophotometer to test within the wavelength range of 200nm to 800nm. Figure 1 This is the photoelectron spectrum of soy protein isolate (SPI). Figure 2 The photoelectron spectrum of the soy protein isolate-based film (SPI / P / D-0) prepared in Comparative Example 3. Figure 1 It can be seen that the N1s spectrum of SPI shows two main peaks at 399.36eV ​​(CN) and 400.6eV (NH). A new C=N characteristic peak was observed in the N1s spectrum of the SPI / P / D-0 film, located at 399.37eV. This confirms that the amino groups in SPI react with the aldehyde groups in dialdehyde starch to form -HC=N- functional groups, that is, a covalent cross-linking network is formed in the soy protein isolate film.

[0098] Figure 3 and Figure 4 The stress-strain curves and toughness bar graphs of the soy protein isolate-based films prepared in the examples and comparative examples are shown respectively. Toughness refers to the ability of a material to absorb energy during plastic deformation and rupture. The better the toughness, the less likely it is to experience brittle fracture. Due to the weak interaction between the SPI molecules and glycerol (G), the SPI / G film of comparative example 1 exhibits poor mechanical strength of 2.5 MPa, an elongation at break of 231%, and a toughness of 4.8 MJ / m 3 Compared with the SPI / G film, the tensile strength of the SPI / P film of comparative example 2 was increased to 7.06MPa, but the elongation at break and toughness were very poor; its elongation at break was 19.16 and its toughness was 1.2MJ / m 3 After cross-linking with dialdehyde starch and soy protein isolate (Comparative Example 3), the toughness of SPI / P / D-0 film increased sharply by 1492% to 19.1 MJ / m 3The tensile strength and elongation at break also increased significantly, reaching 12.79 MPa and 194.95%, respectively. This may be because the amino groups of soy protein isolate reacted with the aldehyde groups of dialdehyde starch to produce covalent crosslinks, and at the same time, the hydroxyl groups of polyvinyl alcohol, the amino and hydroxyl groups of protein, and the hydroxyl groups of dialdehyde starch formed an interconnected crosslinking network in the soy protein isolate-based film through a variety of non-covalent interactions (including hydrogen bonds, hydrophobic interactions, etc.) and covalent bonds, thereby improving the strength and toughness of the film. Although the toughness, tensile strength and elongation at break of the film in Comparative Example 3 are significantly increased by cross-linking dialdehyde starch and soy protein isolate, the structure of the soy protein isolate cannot be fully unfolded due to the lack of the cooperation of the pulsed electric field. The soy protein isolate-based film has few cross-linking sites in toughness, and the covalent cross-linking and non-covalent bonding between protein and aldehyde groups are also weakened. Even the tensile strength of the SPI / P / D-0 film of Comparative Example 3 reaches 12.79±1.2MPa, the elongation at break is 194.95±4.1%, and the toughness is 19.1MJ / m 3 The ultraviolet blocking rate is 97.23%, but the tensile strength of the SPI / P / D-2 film of Example 1, which is relatively inferior to that of the examples, is 13.70±0.51MPa, the elongation at break is 217.71±5.3%, and the toughness is 23.6MJ / m 3 Compared with the ultraviolet blocking rate of 99.04%, there is still a comprehensive gap, and the ultraviolet blocking rate is difficult to meet the requirements of some applications. When the present invention further uses pulsed electric field to assist in the preparation of thin films on the basis of comparative example 3, Examples 1, 2, and 3 are soy protein isolate-based films prepared under electric field strengths of 2kV / cm, 4kV / cm, and 6kV / cm, respectively. The mechanical properties of the films increase with the increase of field strength. The toughness of the SPI / P / D-6 film of Example 3 is 36.2MJ / m 3 Compared with the film without pulse electric field, it increased by 89.5%, and compared with the traditional film with glycerol (SPI / G), it increased by 654%. The tensile strength of SPI / P / D-6 film is 18.28MPa, which is 40.9% higher than that of the film without pulse electric field, and 631% higher than that of the traditional film with glycerol (SPI / G). The effect is very significant.

[0099] The present invention can also accurately control the mechanical properties of the material by adjusting the field strength of the pulse electric field (the energy of the pulse electric field). Under low field strength (<4kV / cm), the toughness of the material can be controlled to be 19-27MJ / m 3 Under medium and high field strength (4-15kV / cm), the toughness of the material can be controlled to 27-25MJ / m 3, to be applied to active packaging materials for different foods. Mainly, the treatment with pulsed electric field unfolds the structure of soy protein isolate, improves the flexibility and toughness of the protein, and exposes more sites for cross-linking with dialdehyde starch, promoting the covalent cross-linking and non-covalent bond (hydrogen bond) interaction between the amino group and the aldehyde group of the protein. Thereby, a soy protein isolate-based film with excellent tensile strength and high toughness is produced. At the same time, the degree of unfolding of the soy protein isolate structure can be controlled by adjusting the magnitude of the pulsed electric field energy, thereby achieving precise control of the size range of the film's mechanical properties. However, when the field strength of PEF is too small (<2kV / cm) or too large (>15kV / cm), such as in Comparative Examples 4 and 5, the tensile strength of the soy protein isolate film is less than 13MPa, and the toughness is ≤20MJ / m 3 , due to the weakened mechanical properties, it is difficult to be well applied to food packaging bags. The SPI / P / D film prepared by the pulse electric field in the present invention exhibits good mechanical properties, and the mechanical properties of the material can be accurately controlled by adjusting the energy of the pulse electric field.

[0100] Figure 5 The ultraviolet blocking performance of the soy protein isolate based films prepared in the examples and comparative examples. The ultraviolet blocking rates of the SPI / G and SPI / P films are 63.3% and 79.02% (<400nm), respectively, while the ultraviolet blocking rate of the film (SPI / P / D-0) cross-linked with dialdehyde starch and soy protein isolate is rapidly increased to 97.23% (<400nm). This remarkable ultraviolet shielding performance is due to the strong absorption of ultraviolet rays by the imine group (C=N) generated by the Schiff base reaction. In Examples 1, 2 and 3, the ultraviolet blocking performance of the soy protein isolate based films prepared with the assistance of pulsed electric fields is above 99% (<400nm). It is confirmed from the side that the pulsed electric field can promote the covalent cross-linking of the amino group and the aldehyde group of the protein to generate more imine groups. However, when the field strength of the PEF is too small (<2kV / cm) or too large (>15), the ultraviolet blocking performance is weakened, all below 99%, and it is not used in ultraviolet protective coatings. For example, it cannot be used in sun protection products such as parasols and outdoor tents.

[0101] The soy protein isolate-based film of the present invention has good mechanical properties and excellent ultraviolet barrier properties, and can therefore replace traditional plastic bags, cling films, etc., and is used for packaging and preserving articles, fruits and vegetables, etc., and can also be used in anti-ultraviolet coating materials.

[0102] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A tough soy protein isolate-based film, characterized in that: The method comprises mixing a soy protein isolate solution, a dialdehyde starch solution and a polyvinyl alcohol solution, adjusting the pH to 8.5-11, reacting the mixture at 60-100° C. and under the action of a pulse electric field for 10-50 minutes, pouring the product into a culture dish and drying the mixture; the frequency of the pulse electric field is 100-1000 Hz, the pulse width is 10-60 μs, and the field strength is 2-15 kV / cm.

2. The tough soy protein isolate-based film according to claim 1, characterized in that: The mass content of the soy protein isolate solution is 1% to 10%.

3. The tough soy protein isolate-based film according to claim 1, characterized in that: The mass content of the dialdehyde starch solution is 4% to 15%.

4. The tough soy protein isolate-based film according to claim 1, characterized in that: The mass content of the polyvinyl alcohol solution is 5% to 20%.

5. The tough soy protein isolate-based film according to claim 1, characterized in that: The mass ratio of the soybean protein isolate to polyvinyl alcohol is 1:0.2-1.5, and the mass ratio of the soybean protein isolate to dialdehyde starch is 2-9:

1.

6. The tough soy protein isolate-based film according to claim 1, characterized in that: The pH value is adjusted to 8.5-11 by adding an alkaline solution, and the concentration of the alkaline solution is 0.05 mol / L-0.3 mol / L.

7. The tough soy protein isolate-based film according to claim 6, characterized in that: The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

8. The tough soy protein isolate-based film according to claim 1, characterized in that: The drying is carried out in an oven at a drying temperature of 30-60° C. and a drying time of 10-30 h.

9. The process for preparing the tough soy protein isolate-based film according to any one of claims 1 to 8 by precise control of a pulse electric field, characterized in that The following steps are involved: 1) Mixing the soy protein isolate solution, the dialdehyde starch solution and the polyvinyl alcohol solution; 2) adjusting the pH to 8.5-11, and pumping the mixed solution into a pulsed electric field at a temperature of 60-100°C for 10-50 minutes; the frequency of the pulsed electric field is 100-1000 Hz, the pulse width is 10-60 μs, and the field strength is 2-15 kV / cm; 3) The product obtained in step 2) is poured into a culture dish and dried to obtain a soy protein isolate-based film.

10. Use of the tough soy protein isolate-based film according to any one of claims 1 to 8 in the preparation of food active packaging or ultraviolet protection materials.

Citation Information

Patent Citations

  • A prolamin-starch-based degradable composite film and preparation method thereof

    CN103627033B

  • Method for preparing high foamability soy protein

    CN102940125A

  • Nano composite soy protein plastic and preparation method thereof

    CN104861662A